The role of Chinese folk ritual music in biodiversity conservation: an ethnobiological perspective from the Lingnan region - Yibo Liu; Yingjie Song (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Traditional ecological knowledge embedded in cultural practices is vital for biodiversity conservation but is increasingly under threat from modernization and globalization. This study investigates the role of Chinese folk ritual music in promoting biodiversity conservation, with a focus on Cantonese Opera and agricultural rituals in the Lingnan region of southern China. Methods We employed literature review, qualitative fieldwork, and ethnographic analysis, including interviews with local musicians and community members, to investigate how Cantonese Opera and agricultural rituals contribute to ecological sustainability by integrating cultural narratives with environmental stewardship. Results The findings reveal three main ways in which Chinese folk ritual music supports biodiversity conservation: (1) fostering ecological understanding through symbolic representations, such as the carp and water buffalo; (2) promoting sustainable practices, including traditional farming techniques and the conservation of wetland ecosystems; and (3) enhancing community cohesion and the transmission of ecological values across generations. Notably, 70% of interviewees highlighted the role of symbolic animals in raising awareness of ecological sustainability. Conclusions The study underscores the potential of integrating traditional ecological knowledge with modern conservation strategies. Cultural traditions, such as Cantonese Opera and agricultural rituals, not only preserve biodiversity but also provide a framework for sustainable resource management. These findings highlight the importance of protecting and revitalizing cultural practices to ensure both cultural and ecological resilience in the face of global challenges.